Rescue morphine in mechanically ventilated newborns associated with combined OPRM1 and COMT genotype. (July 2014) - Matic, Maja; Simons, Sinno HP; van Lingen, Richard A; van Rosmalen, Joost; Elens, Laure; de Wildt, Saskia N; Tibboel, Dick; van Schaik, Ron HN
Aim: Determine whether SNPs of OPRM1 118A>G (asn 40 asp), COMT 472G>A (val 158 met) and ARRB2 8622C>T are associated with morphine rescue in newborns on mechanical ventilation.Materials & methods: This is a pharmacogenetic analysis of a randomized controlled trial in (pre)term newborns (n = 64) at a level III Neonatal Intensive Care Unit (NICU) who received placebo infusion and for whom need and dose for rescue morphine was documented.Results: For OPRM1 and COMT separately, the expected risk for rescue morphine or morphine dose was not significantly increased. However, the combined OPRM1/COMT 'high-risk' genotype lead to a significant association with the need for rescue (OR: 5.12; 95% CI: 1.12–23.3; p = 0.035). No association was found between OPRM1/COMT 'high-risk' genotype and total morphine dose administered.Conclusion: Combined OPRM1 118A>G and COMT 472G>A genotype might serve as a predictor for the need of rescue morphine in premature and term newborns on mechanical ventilation. Original submitted 21 January 2014; Revision submitted 20 June 2014